2010
DOI: 10.1002/rra.1457
|View full text |Cite
|
Sign up to set email alerts
|

Quasi‐equilibrium conditions of urban gravel‐bed stream channels in southern Ontario, Canada

Abstract: Urban gravel‐bed stream channels in southern Ontario, Canada identified to be in a state of quasi‐equilibrium have been studied over the past 15 years and compared against rural gravel bed stream channels of the same hydrophysiographic region. Bankfull width and depth versus bankfull discharge were not found to increase as a function of increasing urbanization as has been found in many other studies. The observed annual frequency of bankfull discharge was typically less than a 1‐year return period with many si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 65 publications
2
26
0
Order By: Relevance
“…However, not all HLRs with lower numbers of sites produced poorer fits (e.g., HLRs 1,3,15,and 19). The higher levels of variability associated with bankfull parameters is possibly linked to landscape factors such as the number and location of reservoirs upgradient in the watershed (Deitch et al, 2013), level of irrigation or water withdrawal within the watershed (Kendy and Bredehoeft, 2006;Caskey et al, 2014), reliance or lack thereof on snowmelt (USGS, 2005;Miller and Piechota, 2011), type of streamside vegetation (Hession et al, 2003), and degree of urbanization (Doll et al, 2002;Cianfrani et al, 2006;Annable et al, 2010). These factors may have influenced assessed streams unequally within and across these arid and semiarid HLRs, more so than the humid and subhumid HLRs.…”
Section: Regionalizationmentioning
confidence: 99%
“…However, not all HLRs with lower numbers of sites produced poorer fits (e.g., HLRs 1,3,15,and 19). The higher levels of variability associated with bankfull parameters is possibly linked to landscape factors such as the number and location of reservoirs upgradient in the watershed (Deitch et al, 2013), level of irrigation or water withdrawal within the watershed (Kendy and Bredehoeft, 2006;Caskey et al, 2014), reliance or lack thereof on snowmelt (USGS, 2005;Miller and Piechota, 2011), type of streamside vegetation (Hession et al, 2003), and degree of urbanization (Doll et al, 2002;Cianfrani et al, 2006;Annable et al, 2010). These factors may have influenced assessed streams unequally within and across these arid and semiarid HLRs, more so than the humid and subhumid HLRs.…”
Section: Regionalizationmentioning
confidence: 99%
“…This model has been used to help interpret channel responses to urbanization whether through incision or channel widening (Henshaw and Booth, 2000;Hardison et al, 2009) even while it has become clear that it may not apply equally in all contexts Booth and Fischenich, 2015). If floodplain connectedness can be maintained, incision may be avoided, thereby averting the initiation of the cycle entirely (Hardison et al, 2009;Annable et al, 2012). If floodplain connectedness can be maintained, incision may be avoided, thereby averting the initiation of the cycle entirely (Hardison et al, 2009;Annable et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Available evidence suggests that an initial aggradational response of approximately 15 years due to increased sediment loads (Wolman and Schick, 1967) is followed by channel enlargement over anywhere from 5 to over 50 years posturbanization (Chin, 2006), though a wide range of adjustment periods have been observed (Henshaw and Booth, 2000;Hardison et al, 2009;Annable et al, 2012). Available evidence suggests that an initial aggradational response of approximately 15 years due to increased sediment loads (Wolman and Schick, 1967) is followed by channel enlargement over anywhere from 5 to over 50 years posturbanization (Chin, 2006), though a wide range of adjustment periods have been observed (Henshaw and Booth, 2000;Hardison et al, 2009;Annable et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Both Cianfrani et al [55] and Doll et al [56] found that urbanization increased bankfull channel width as compared to rural streams in the Piedmont region of the U.S. Contrary, Annable et al [57] found that urbanization did not result in significant channel enlargement for streams in Ontario, Canada. In this study, no trends between percent imperviousness and bankfull width were found for the Outer Bluegrass (Figure 10), so it is likely that the level of urbanization is not the controlling factor for bankfull width.…”
Section: Bankfull Hydraulic Geometry Curvesmentioning
confidence: 95%